Effects of β‐hydroxy β‐methylbutyrate (HMB) supplementation on muscle mass, function, and other outcomes in patients with cancer: a systematic review. Issue 3 (17th March 2022) - Prado, Carla M.; Orsso, Camila E.; Pereira, Suzette L.; Atherton, Philip J.; Deutz, Nicolaas E. P.
Abstract: Low muscle mass is prevalent among patients with cancer and a predictor of adverse clinical outcomes. To counteract muscle loss, β‐hydroxy β‐methylbutyrate (HMB) supplementation has been proposed as a potential therapy for older adults and various diseases states. This systematic review aimed to investigate the effects and safety of HMB supplementation in relation to muscle mass and function and other clinical outcomes in patients with cancer. A systematic search of MEDLINE, CINAHL, Embase, Cochrane Central Register of Controlled Trials, Scopus, ProQuest, and grey literature for reports published from inception to December 2021 was conducted. Included studies provided supplements containing any dose of HMB to adult patients with active cancer. A synthesis without meta‐analysis was conducted using a vote‐counting approach based solely on the direction of the effect (i.e. regardless of statistical significance). Risk of bias was assessed for each outcome domain, and evidence from higher‐quality studies (i.e. those with either low or moderate risk of bias) was examined. Safety was evaluated using both lower‐quality and higher‐quality studies. Fifteen studies were included, in which six were randomized controlled trials in patients with various cancer types and treatments. Studies prescribed HMB combined with amino acids (73.3%), HMB in oral nutritional supplements (20.0%), or both supplement types (6.7%); Ca‐HMB doses of 3.0 g/day were provided in 80.0% of the studies. Four studies had high risk of bias across all outcome domains. Considering the higher‐quality studies, evidence of a beneficial effect of HMB supplementation was found in four of four studies for muscle mass, two of two for muscle function, three of three for hospitalization, and five of seven for survival. In contrast, no beneficial effects of HMB on quality of life or body weight was found in two of four and three of five studies, respectively. A limited number of higher‐quality studies evaluating the impact of HMB on cancer therapy‐related toxicity, inflammation, and tumour response were observed. No serious adverse effects directly related to the nutrition intervention were reported. Although limited, current evidence suggests that HMB supplementation has a beneficial effect on muscle mass and function in patients with cancer. Well‐designed trials are needed to further explore the clinical benefit of HMB supplementation in this patient population.